Atomic-scale marriage of light-harvesting and charge-storing components for efficient photoenergy storage catalysis. (October 2016) - Xu, Yingfeng; Lu, Ping; Chen, Lisong; Zhang, Chen; Zhang, Lingxia; Zhang, Xiaohua; Shi, Jianlin
Abstract: Photoenergy storage catalyst, conventionally constructed by combining a light harvesting component with a charge-storage material, could store partial of photoexcited charge carriers (e − /h + ) under illumination and release them in dark, which is regarded as one of the most promising strategies to compensate the fluctuating availability of solar energy. However, the charge storage efficiency of most reported heterojunctions is quite limited due to the interfacial defects that would quickly quench the photoexcited e − /h + pairs and hinder the charge transfer. Here, through precisely regulating the hydrolysis and condensation kinetics of titanic and molybdate chemical compounds, {Mo(VI)O x } component was incorporated into TiO2 matrix to construct an artificial atomic-scale heterojunction for photoenergy storage (denoted as Mo-TiO2 ). In contrast to the conventional nano-scale heterojunction, the absence of defined interfaces in Mo-TiO2 enables an improved transfer of photoexcited electrons from TiO2 to {Mo(VI)O x }, leading to an efficient photoenergy storage process under illumination. Then, the stored electrons can spontaneously be released after light turning-off, achieving a dark-continued catalytic activity. The present atomic-scale heterojunction strategy may open up a new dimension for the design and construction of practical photoenergy storage systems. Graphical abstract: Incorporation of the charge-storing {Mo(VI)O x } component into TiO2 matrix to construct an atomic-scale heterojunction for photoenergy storage catalysis. Highlights: Construct a novel atomic-scale heterojunction for photoenergy storage catalysis. Incorporate charge-storing {Mo(VI)O x } component into light-harvesting TiO2 . High-performance for photocatalyzed and dark-continued pollutant decomposition.